Natural Law in Cicero - Direito, Carlos Gustavo Vianna (Romanitas - Revista de Estudos Grecolatinos, 2026)
This research aims to understand Cicero’s philosophical contribution to the theory of natural law. Among the three major classical schools of thought on natural law (Platonic, Aristotelian, and Stoic), Cicero joined the natural law tradition inaugurated by Plato. Written in the late 50s BCE, inspired by Plato’s Laws, De Legibus represents Cicero’s principal effort in the philosophical theorization of law. Law, rooted in nature and right reason, represents an objective criterion for the universal validation of positive norms. By associating natural law with the virtue of prudence, Cicero signaled that natural reason was closely linked to the Roman tradition of iurisprudentia, articulating Platonic and Stoic foundations in an original theory of natural law that consolidated a theoretical framework for subsequent philosophical debate.